THE EFFECTS OF N-ACETYLCYSTEINE ON NOISE INDUCED HEARING LOSS :A SYSTEMATIC REVIEW - Omasih Kiantimi, Ni Putu; Yoga, I Made; Pringga Dewi Astuti, Ni Nyoman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: A preventable cause of sensorineural hearing loss (SNHL) is noise-induced hearing loss (NIHL). An essential factor in the pathophysiology of NIHL is oxidative stress. NAC is associated with its antioxidant and anti-inflammatory activity, which favors the maintenance of a cellular redox imbalance. As such, its potential for treatment relates to several diseases whose origins and progression are linked to oxidative stress. The aim: This study aims to show the effect of N-Acetyl-Cysteine on sensorineural hearing loss. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2008 and 2023 were taken into account. Several different online reference sources, like Pubmed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 37 articles, whereas the results of our search on ScienceDirect brought up 38 articles. The results of the search conducted by screening yielded a total 6 articles for PubMed and 1 article for ScienceDirect. We excluded 1 article having ineligible intervention, and 1 article having ineligible outcomes data. In the end, we included five research that met the criteria. Conclusion: We found positive results in most of the studies, N-acetylcysteine showed better effect on reducing hearing loss and increasing hearing recovery in NIHL and the most common adverse events symptoms reported were gastrointestinal.